Regarding the names of the epidemics - Bochnakowa, Anna (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
The article is devoted to the names of epidemics that have affected many countries in Europe and the world over the centuries. After a short historical introduction, French and Polish names will be presented along with the information about their etymology: choléra / cholera, dysenterie / czerwonka, ébola / ebola, fièvre jaune / żółta febra, grippe / grypa, lèpre / trąd, peste / dżuma, rougeole / odra, syphilis / kiła, tuberculose / gruźlica, typhus / tyfus, variole / ospa, SRAS / SARS Covid 19. The names mostly date back to before the nineteenth century, when the causes of diseases began to be scientifically researched and treated. Most French names are book terms of Greek-Latin origin. Half of the Polish names are Slavic. This proves that the ancient Latin medical literature in Poland is less extensive and that folk names are common. The names of contemporary diseases are often abbreviated English names.